Art and architecture of the synagogue in byzantine palaestina - Friedman, Asaf (CAMBRIDGE SCHOLARS Publishing, 2019)
The Byzantine era was a time of the formation of the Abrahamic religions and a battleground for people's hearts and minds. This book shows that, during the time of the Byzantine Empire, the synagogues in Palaestina developed a visual language adhering to traditional literary sources. Until now, scholars believed that Judaism was oblivious to all art forms, regarding them as mere ""decoration."" This book shows that, contrary to those beliefs, Jewish art was, in fact, flourishing in this period. The visual language that emerged is a trope that utilizes literal and figurative readings to arrive.